Spatiotemporal Variations in Surface Heat Loss Imply a Heterogeneous Mantle Cooling History. Issue 6 (24th March 2021) - Karlsen, Krister S.; Conrad, Clinton P.; Domeier, Mathew; Trønnes, Reidar G.
Abstract: Earth's heat budget is strongly influenced by spatial and temporal variations in surface heat flow caused by plate tectonic cycles. Here, we use a novel set of paleo‐seafloor age grids extending back to the mid‐Paleozoic to infer spatiotemporal variations in surface heat loss. The time‐averaged oceanic heat flow is 36.6 TW, or ∼25% greater than at present‐day. Our thermal budget for the mantle indicates that 149 K/Gyr of cooling occurred over this period, consistent with geochemical estimates of mantle cooling for the past 1 Gyr. Our analysis also suggests sustained rapid cooling of the Pacific mantle hemisphere, which may have cooled ∼50 K more than its African counterpart since 400 Ma. The extra heat released from the Pacific mantle may have been trapped there by the earlier long‐lived supercontinent Rodinia (∼1.1–0.7 Ga), and the Pacific mantle may still be hotter than the African mantle today. Plain Language Summary: Earth's interior is cooling because its rate of heat loss exceeds its rate of internal heat production. Heat loss happens at the Earth's surface and is highly variable, with thick continents providing strong insulation to Earth's interior and thin seafloor allowing more rapid heat transfer. Using models for how the continents and oceanic plates have moved for the past 400 million years, we reconstructed the history of heat loss from Earth's interior. We find that heat loss was on average 25% higher in the past than it is today, which implies more rapid overall cooling than expected. We also find that the Pacific side of the world has lost heat at a much faster rate than the African side. This is partly due to positioning of continental landmasses, including the supercontinent Pangea, on the African side for most of the past 400 million years. By contrast, the oceans on the Pacific side offered "poor insulation" that led to ∼50 °C more cooling of the Pacific mantle compared to its African counterpart. The extra heat lost from the Pacific side may have been trapped there by Rodinia, an older, long‐lived supercontinent that covered the Pacific mantle about one billion years ago. Key Points: We use novel paleo‐seafloor age grids covering the past 400 Myr to quantify spatial and temporal variations in mantle heat loss The time‐averaged oceanic heat flow over the past 400 Myr is 36.6 TW, which is ∼25% greater than at present‐day The Pacific hemisphere has been cooling much faster than the African, possibly releasing heat trapped by the earlier supercontinent Rodinia